Development of a Biodegradable Detergent Based on Quinoa as an Alternative to Minimize Eutrophication - Yupanqui Pacheco, Karina (2024)
Synthetic detergents were created more than a century ago and their use has been essential, however, during the SARS-CoV-2 pandemic, the Ministry of Health issued recommendations for hygiene and disinfection in which the use of these detergents was further enhanced. Due to this problem, it was proposed to develop a biodegradable detergent with low concentrations of compounds containing phosphorus and nitrogen, in order to minimize eutrophication in surface bodies that cause ecosystemic imbalances. The experiment consisted of washing two garments in the same conditions (dirty) and each one with each detergent (conventional and biodegradable), as a result it was obtained that both garments were clean after washing. For the laboratory analysis, wastewater samples were taken from each container. The results obtained from the laboratory were as follows: the conventional detergent had the following concentrations: pH (11.25), T° (12.3 °C), Conductivity (11,350 uS/cm), Phosphorus (4.11 mg/L) and total Nitrogen (20.16 mg/L); while for the biodegradable detergent the resulting concentrations were: pH (7.02), T° (12.6 °C), Conductivity (445 uS/cm), Phosphorus (0.318 mg/L) and total Nitrogen (<1.00 mg/L). Finally, the biodegradable detergent proved to have the same efficiency and minimize eutrophication.